Molecular changes associated with the origin of centrosome amplification in human cancer - Nunes, Leonor Ferreira dos Santos Pereira (2022)
The centrosome plays a critical role in maintaining cellular homeostasis by actively participating in microtubule nucleation, cell division, polarity, signaling and migration. Abnormalities in centrosome structure or number, including centrosome amplification, are a hallmark of human cancer. Centrosome amplification has been shown to predict high-grade malignancy and poor prognosis for patients, however, the fact that its origins are poorly understood limits its clinical use. In a previous report, using the unique Barrett’s esophagus human cancer model, it was determined that centrosome amplification arises early in tumorigenesis, still in the pre-malignant stage. Following this, we confirmed that four centrosomal proteins are deregulated through these early stages. The distinct pathways known to be promoted by their deregulation suggest that multiple mechanisms could be driving centrosome amplification. This is further supported by our analysis of the ratio of mother to daughter centrioles in cells presenting amplification. Additionally, in our study, we revealed a deregulation of two core components of the centriolar appendages in the early stages of tumorigenesis. Further investigation is warranted to dissect the full spectrum of centrosomal deregulations and their origin in human tumorigenesis. This could uncover prognostic markers impacting the current strategies of cancer management, including Barrett’s esophagus neoplasia.